Elaboramos un croquis para organizar el mobiliario del aula - Díaz Ramírez, Etelda Noemí (2019)
The present work of professional sufficiency called "We elaborate sketches" has been prepared to apply it in a section of fourth grade of primary education of the I.E. N°81015 "Carlos Emilio Uceda Meza" of the city of Trujillo._x000D_ The first part is oriented to the planning of the learning session where the learning purposes are considered as the competence: Solve problems of movement and location, the abilities Use strategies and performance: Express with graphics or sketches the displacements and positions of nearby objects, people and places, as well as their translations in relation to fixed objects as reference points._x000D_ The didactic processes of the area have also been considered, proposing strategies that involve students at all times, in order to obtain meaningful learning._x000D_ In the second part, theoretical support is considered, where some key definitions of the topic to be treated to support this work are explained._x000D_ In the third part the pedagogical support is detailed, where it is explained what is the mathematics, the approach that sustains the development of the competences of the area, the corresponding competence, as well as the didactic and pedagogical processes according to the National Curricular Design.